Growth-stimulating effect of ferric citrate on hybridoma cells: characterization and relation to transferrin function - Kovár, J (Hybridoma, 1988)
The growth of mouse hybridomas in the defined medium with ferric citrate at the optimum growth-stimulating concentration of 500 microM in place of transferrin is fully comparable with the growth in the medium with transferrin at the optimum concentration of 5 micrograms/ml. Experiments with monoclonal antibody to mouse transferrin receptor demonstrate that the growth-stimulating effect of ferric citrate is not based on the action of residual transferrin or the action of transferrin secreted by hybridoma cells. Such growth-stimulating effect is specific for iron compounds while other metal trace elements are ineffective. Hybridoma cells can absorb iron from medium containing iron salt without the presence of transferrin.
Keywords: Cattle; transferin; Animals; skot; Hybridomas; druhová specificita; železité sloučeniny; Growth Substances; lidé; hybridomy; Mice; Species Specificity; prasata; Transferrin; myši; Swine; růstové látky; zvířata; Ferric Compounds; Humans